An empirical analysis of effects of foreign direct investment, exchange rate and energy infrastructure on domestic investment in Nigeria - Adekunle, Ahmed O.; Abdullahi, Bello I.; Gbadebo, Adedeji D.; Fakunmoju, Segun K. (Journal of Management, Economics, and Industrial Organization, 2019)
Domestic investment is a significant component of economic activities affecting Nigerian economy for decades. Sequel to this, this paper examines the effect of Foreign Direct Investment (FDI), exchange rate and energy infrastructure on domestic investment in Nigeria. Time series data obtained from Central Bank of Nigeria (CBN) Statistical Bulletin and World Development Indicator were employed using Autoregressive Distributive Lag (ARDL) Model. Empirical findings show that FDI has positive and significant effect on domestic investment while exchange rate and energy infrastructure have a positive effect on domestic investment but non significant. The policy implications of this finding is that government should adopt more stringent supervision on exchange rate, and policy to regulate execution of energy infrastructure project; and more funds needed to emancipate energy infrastructure in order to obtain desired level of domestic investment in Nigeria.